2012
DOI: 10.1007/s00464-011-2137-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colorectal resection for cancer: effects of conversion on long-term oncologic outcomes

Abstract: Conversion to open surgery does not affect oncologic outcomes, although CONV patients have increased comorbidity rates affecting long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 18 publications
1
43
0
1
Order By: Relevance
“…However, the interpretation of these results is limited by the small and heterogeneous groups of patients considered because many studies have included benign diseases such as diverticulitis and inflammatory bowel disease besides colorectal cancers. Data restricted to cancer patients are more controversial [3,17,19,20,22]. Whereas some authors [3,17] have observed that patients undergoing conversion had significantly higher rates of blood transfusions, surgical complications including anastomotic leakage, and reintervention than patients who had a completed LCR, others did not find adverse effects of conversion on the early postoperative outcomes for patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the interpretation of these results is limited by the small and heterogeneous groups of patients considered because many studies have included benign diseases such as diverticulitis and inflammatory bowel disease besides colorectal cancers. Data restricted to cancer patients are more controversial [3,17,19,20,22]. Whereas some authors [3,17] have observed that patients undergoing conversion had significantly higher rates of blood transfusions, surgical complications including anastomotic leakage, and reintervention than patients who had a completed LCR, others did not find adverse effects of conversion on the early postoperative outcomes for patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported higher morbidity and mortality rates and a longer postoperative hospital stay [3,[13][14][15][16][17][18], whereas others did not find significant differences in comparisons with to non converted patients [12,[19][20][21][22]. The oncologic outcomes for converted patients are poorly investigated, and the data currently available are unclear [10,[12][13][14][15][16][17][18][19][20][21][22][23]. This study aimed to evaluate the impact of conversion to open surgery on short-and long-term outcomes in a large series of patients undergoing laparoscopic resection for nonmetastatic colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The full text of the remaining 79 articles was examined in more detail. After excluding 59 studies, 20 studies [11,12,15,16,18,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] were included in the meta-analysis (Fig. 1 [11,16,22,26,27].…”
Section: Study Selectionmentioning
confidence: 99%
“…Rottoli et al [29] Laparotomy created for any purpose other than specimen extraction Senagore et al [23] n . d .…”
Section: Study Selectionmentioning
confidence: 99%
“…Einige Studien hierzu zeigen keinen Unterschied im Outcome nach Konversion [17,18]. Im Gegensatz hierzu bestätigen die Daten der 3- und 5-Jahres-Analyse der CLASICC-Studie ein schlechteres Outcome nach Konversion, was sich jedoch statistisch «lediglich» im Gesamtüberleben signifikant unterschiedlich zeigte [9,14].…”
Section: Diskussionunclassified